Characterisation of focused gas hydrate accumulations from the Pegasus Basin, New Zealand, using high-resolution and conventional seismic data. Issue 1 (1st December 2018) - Gorman, Andrew R.; Fletcher, Patrick T.; Baker, Dylan; Fraser, Douglas R.A.; Crutchley, Gareth J.; Henrys, Stuart A.
Abstract : Gas hydrates are reported widely in seismic data from New Zealand's Hikurangi Margin (east coast of the North Island). Over the last decade, conventional petroleum exploration interests in this region have led to the collection of several regional seismic datasets. These data have greatly improved our understanding of hydrate accumulations in the area; however, the resolution of industry multichannel seismic surveys is limited by the bandwidth of the airgun sources used. We present preliminary results from an academic high-resolution generator-injector (GI) airgun seismic survey, undertaken in mid 2015, that targeted focused gas hydrate accumulations lying within thrusted accretionary units in the Pegasus Basin, at the south end of the Hikurangi Margin. Each feature was surveyed with 5 to 10 closely spaced seismic lines that provide an opportunity to examine the three-dimensional structure and stratigraphy with better resolution than the original lines. Two main processes of natural gas migration and resulting accumulation as hydrate are examined more fully: (1) vertical transport into the shallow seafloor driven by overpressure and (2) inclined transport upward along dipping permeable beds. In both of these cases, our data show significant three-dimensional variability is needed to focus fluid migration from below into hydrate trapping configurations within the hydrate stability field nearer to the seafloor. Due to the absence of well data in this basin, the high-resolution seismic data also help to constrain interpretations of basin stratigraphy which plays a significant role in hosting and trapping hydrate accumulations.